ENHANCING THE LEGAL FRAMEWORK TO PROTECT THE MINIMUM STANDARD OF LIVING AND STRENGTHEN SOCIAL SAFEGUARDS FOR DEBTORS DURING ENFORCEMENT PROCEEDINGS - Atadjanov Zafarbek Alisherovich (Bright Mind Publishing, 2025)
There is a growing need to systematize and further improve legislation on the execution of judicial decisions and documents from other authorities. This legislation aims to reduce the human factor in the enforcement process, while guaranteeing the inviolability of property and funds necessary to ensure citizens' minimum standard of living.
Keywords: Law, Bureau of Compulsory Enforcement, court documents, debt, property, wages, cash funds, bank, deposit, required amount, guarantee, minimum standard of living, human factor.